Designing double-site lipidated peptide amphiphiles as potent antimicrobial biomaterials to combat multidrug-resistant bacteria - Lai, Zhenheng; Chen, Hongyu; Yuan, Xiaojie; Tian, Jiahui; Dong, Na; Feng, Xingjun; Shan, Anshan (Frontiers in Microbiology, 2022)
Rapidly evolving antimicrobial resistance and extremely slow development of new antibiotics have resulted in multidrug-resistant bacterial infections that present a serious threat to human health. Antimicrobial peptides (AMPs) provide promising substitutes, but more research is needed to address several of their present limitations, such as insufficient antimicrobial potency, high toxicity, and low stability. Here, we designed a series of novel double-site lipidated peptide amphiphiles based on a heptad repeat parent pentadecapeptide. The double-site lipidated peptide amphiphiles showed a broad spectrum of antimicrobial activities. Especially the double-site lipidated peptide amphiphile WL-C6 exhibited high potency to inhibit multidrug-resistant bacteria without significant toxicity toward mammalian cells. Furthermore, even at physiological salt ion concentrations, WL-C6 still exhibited outstanding antibacterial properties, and a sizeable fraction of it maintained its molecular integrity after being incubated with different proteases. Additionally, we captured the entire process of WL-C6 killing bacteria and showed that the rapid bacterial membrane disruption is the reason of bacterial death. Overall, WL-C6 shows great promise as a substitute for conventional antibiotics to combat the growing threat of multidrug-resistant bacterial infections.